(untitled) (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2019)
Abstract:Â Ventriculoperitoneal (VP) shunt placement is one of the most commonly performed procedures in neurosurgery. One rare complication is the formation of an abdominal pseudocyst, which can cause shunt malfunction. Â